Simbolisme Perempuan dan Alam dalam Puisi “Jeritan Perempuan yang Melawan” Karya Nolinia Zega (Kajian Ekofeminisme) - Hana Khairiyah; Dwi Wahyu Candra Dewi; Muhammad Rafiek; Nurul Huda (Integrated Education Journal, 2024)
This study analyzes the poem "Jeritan Perempuan yang Melawan" by Nolinia Zega using a qualitative method with an ecofeminist approach. The research focuses on the representation of the relationship between women and nature expressed through symbolism in the poem. Data were collected through documentation, reading, and note-taking techniques, with textual excerpts as the primary source. The analysis reveals that the poem reflects the exploitation of women and nature as a consequence of patriarchal systems. Symbolisms such as the body, fire, and landscape illustrate the resilience of women, paralleling the regenerative capacity of nature. Through these symbols, the poem critiques structural injustices that oppress women and damage the environment. This research affirms that poetry serves not only as an aesthetic medium but also as a tool for articulating social and ecological criticism. The ecofeminist approach provides new insights into how literature can bridge ecological awareness and gender justice.